Asymmetric Hydrogenation: Design of Chiral Ligands and Transition Metal Complexes. Synthetic and Industrial Applications. Issue 7 (29th April 2021) - Genêt, Jean‐Pierre; Phansavath, Phannarath; Ratovelomanana‐Vidal, Virginie
Abstract: This personal account focuses on the development of atropisomeric ligands and chiral transition metal complexes and their applications to the asymmetric hydrogenation of alkenes, ketones and heteroaromatics using Ru(II) and Ir(III) catalysts in‐house developed. Particularly, effective scaled‐up development syntheses of SYNPHOS and DIFLUORPHOS have been successfully achieved and their steric and electronic profiling established. Going further, we demonstrated the utility of such homogeneous catalytic process highlighted with examples of industrial applications and total syntheses of biorelevant targets. Asymmetric hydrogenation provides a powerful tool for performing precise stereocontrolled transformations on valuable complex molecules. Abstract :